2020
DOI: 10.1038/s41388-020-1259-7
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the nuclear Wnt pathway effector TCF7L2 promotes migration and invasion of human colorectal cancer cells

Abstract: The transcription factor TCF7L2 is indispensable for intestinal tissue homeostasis where it transmits mitogenic Wnt/ β-Catenin signals in stem and progenitor cells, from which intestinal tumors arise. Yet, TCF7L2 belongs to the most frequently mutated genes in colorectal cancer (CRC), and tumor-suppressive functions of TCF7L2 were proposed. This apparent paradox warrants to clarify the role of TCF7L2 in colorectal carcinogenesis. Here, we investigated TCF7L2 dependence/independence of CRC cells and the cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
81
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 80 publications
4
81
0
1
Order By: Relevance
“…For subtype c1, 318 DEGs (161 up-regulated and 157 downregulated) were associated with subtype c1, enriched in many important pathways such as DNA replication, cell cycle, mismatch repair, and p53 signaling pathway, and so on, which suggested that subtype c1 had abnormal cell cycle process and p53 signaling pathway dysregulation. Besides, subtypes c1 had the characteristic of high frequent copy loss of TCF7L2 which can promote migration and invasion of human colorectal cancer cells reported by the latest study [39]. High frequent copy loss of RPL18P1 was also found in subtype c1, which could also play important roles in subtype c1.…”
Section: Discussionmentioning
confidence: 78%
“…For subtype c1, 318 DEGs (161 up-regulated and 157 downregulated) were associated with subtype c1, enriched in many important pathways such as DNA replication, cell cycle, mismatch repair, and p53 signaling pathway, and so on, which suggested that subtype c1 had abnormal cell cycle process and p53 signaling pathway dysregulation. Besides, subtypes c1 had the characteristic of high frequent copy loss of TCF7L2 which can promote migration and invasion of human colorectal cancer cells reported by the latest study [39]. High frequent copy loss of RPL18P1 was also found in subtype c1, which could also play important roles in subtype c1.…”
Section: Discussionmentioning
confidence: 78%
“…8B ) may also be applicable to a broader cell lineage. Beyond its role in CNS oligodendroglial lineage, the Wnt effector TCF7l2 regulates a spectrum of biological processes of other lineage cells, such as hepatic metabolism (Boj et al, 2012), colorectal tumor genesis (Angus-Hill et al, 2011; Wenzel et al, 2020), adipocyte function (Chen et al, 2018), and heart development (Ye et al, 2019) where BMP signaling plays crucial roles (Brazil et al, 2015; Wang et al, 2014). The connection between TCF7l2 and autocrine BMP4 signaling has not been reported in these cell types.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we generated a novel prognostic model based on a mutational signature classi er to predict the CRC overall survival and the e cacy of immunotherapy. The mutational signature classi er consisted of 27 mutated genes including APC and TCF7L2 that are relevant to the WNT signaling pathway and in uence the cancer cell metastatic ability [41][42][43], and BRAF and NRAS that are involved in the EGFR signaling pathway and associated with drug-resistance [44][45][46][47]. Using the generated prognostic model, the CRC patients from the cohorts were categorized into high-and low-risk groups.…”
Section: Discussionmentioning
confidence: 99%